Facile and Scalable Synthesis of Nanoporous Materials Based on Poly(ionic liquid)s. Issue 12 (12th September 2014) - Azcune, Itxaso; García, Ignacio; Carrasco, Pedro M.; Genua, Aratz; Tanczyk, Marek; Jaschik, Manfred; Warmuzinski, Krzysztof; Cabañero, Germán; Odriozola, Ibon
Abstract A simple, fast, sustainable, and scalable strategy to prepare nanoporous materials based on poly(ionic liquid)s (PILs) is presented. The synthetic strategy relies on the radical polymerization of crosslinker‐type ionic liquid (IL) monomers in the presence of an analogous IL, which acts as a porogenic solvent. This IL can be extracted easily after polymerization and recycled for further use. The great advantages of this synthetic approach are the atom‐efficiency and lack of waste. The effects of different monomer/porogen ratios on the specific surface area, porosity, and pore size have been investigated. Finally, the potential of the materials as CO2 sorbents has been evaluated.